Perspektif Wahdaniyah Muhammad Nafis Bin Idris Dalam Menanamkan Aqidah Pada Santri Di Pondok Pesantren Insan Madani - Ahmad Ardhi Mauluddin Sitorus; Ira Suryani (Departement of Mathematics Education, 2025)
Wahdaniyah is one of the 20 qualities of Allah SWT that Muslims must know. Wahdaniyah means the Oneness of Allah SWT, namely that Allah has a single and innumerable nature. Wahdaniyah needs to be instilled in today's children, especially children in Islamic boarding schools. This is because education at Islamic boarding schools prioritizes religious education compared to general knowledge. Islamic boarding schools also instill aqidah in their students through education taught at school. This research uses a library method to obtain existing data contained in the Ad-durun An-nafis book about wahdaniyah, then uses a qualitative method of observation to dig deeper into the phenomena that occur in the field, specifically at the Tahfiz Koran Insan Islamic boarding school Madani.